Price incentives, non-price factors, and agricultural production in Sub-Saharan Africa: a cointegration analysis - Rainer Thiele (Kiel Institute for World Economics (IfW), 2002)
This paper deals with the question of how responsive farmers in Sub-Saharan Africa (SSA) are to changes in incentives. Employing Johansen's multivariate cointegration approach, it investigates for ten selected SSA countries the long-run effect of pricing policies, macroeconomic distortions, and certain non-price factors on agricultural production. It turns out that – in those cases where cointegration relationships are found – estimated supply elasticities tend to lie between 0.20 and 0.50. Among the non-price factors, drought episodes have significantly impaired agricultural growth in six out of ten sample countries.
Keywords: C22; Q11; 330; cointegration; Sub-Saharan Africa; agricultural supply response; Agrarproduktion; Landwirtschaft; Angebot; Elastizität; Ökonomischer Anreiz; Kointegration; Schätzung; Zentralafrika